Improvement of Planning Skills in Children With Autism Spectrum Disorder After an Educational Intervention: A Study From a Mixed Methods Approach - Escolano-Pérez, Elena; Acero-Ferrero, Marian; Herrero-Nivela, Mª Luisa (Frontiers in Psychology, 2019)
The literature confirms that individuals with Autism Spectrum Disorder (ASD) have planning deficits. However, few interventions have targeted these deficits. The aims of this pilot study were: 1) show that the mixed methods approach can be useful in studying planning skills of children with ASD during and after an educational intervention; 2) assess whether the planning skills of two groups of children with ASD improved during the intervention and if this progress was maintained one month after completing the intervention. The groups were formed depending on each child's severity level (SL) of ASD according to DSM-5: SL1 (requiring support) and SL2 (requiring substantial support). Each group was composed of four children. In the framework of mixed methods, we used observational methodology which is considered as mixed methods in itself because it integrates qualitative and quantitative elements. A Nomothetic/Follow-up/Multidimensional observational design was used. Planning skills manifested by children during the intervention were codified, as well as the scaffolding behaviors provided by the educational specialist. These skills and behaviors were also coded in one session which took place one month after the intervention. Coded data of each group were submitted to prospective and retrospective lag sequential analysis. This informed of the sequential structure of planning skills performed by children in interaction with the educational specialist at the beginning and at the end of the intervention, as well as one month later after the intervention. The comparison of the patterns obtained in these 3 temporal moments allowed us to know the improvement of the two groups in the use of planning skills. Results showed that both groups improved their autonomous use of planning skills. However, SL1 group used successfully and autonomously complex planning skills while SL2 group were unable to achieve this gain. SL2 group progressed in autonomy, but only using basic planning skills. Both groups can further improve their use of planning skills; therefore, the intervention should be adjusted to their characteristics and temporarily extended. These findings contribute to the, as yet, little studied field of intervention and assessment of planning skills in children with ASD using a mixed methods approach.